Comparative Analysis of Ca2+/Cation Antiporter Gene Family in Rosa roxburghii and Enhanced Calcium Stress Tolerance via Heterologous Expression of RrCAX1a in Tobacco - Tuo Zeng; Liyong Zhu; Wenwen Su; Lei Gu; Hongcheng Wang; Xuye Du; Bin Zhu; Caiyun Wang; Di Wu (Plants)
Rosa roxburghii, a calciphilic species native to the mountainous regions of Southwest China, is renowned for its high vitamin C and bioactive components, making it valuable for culinary and medicinal uses. This species exhibits remarkable tolerance to the high-calcium conditions typical of karst terrains. However, the underlying mechanisms of this calcium resilience remain unclear. The Ca2+/cation antiporter (CaCA) superfamily plays a vital role in the transport of Ca2+ and other cations and is crucial for plant tolerance to metal stress. However, the roles and evolutionary significance of the CaCA superfamily members in R. roxburghii remain poorly understood. This study identified 22 CaCA superfamily genes in R. roxburghii, categorized into four subfamilies. The gene structures of these RrCaCAs show considerable conservation across related species. Selection pressure analysis revealed that all RrCaCAs are subject to purifying selection. The promoter regions of these genes contain numerous hormone-responsive and stress-related elements. qRT-PCR analyses demonstrated that H+/cation exchanger (CAX) RrCAX1a and RrCAX3a were highly responsive to Ca2+ stress, cation/Ca2+ exchanger (CCX) RrCCX4 to Mg2+ stress, and RrCCX11a to Na+ stress. Subcellular localization indicated that RrCAX1a is localized to the plant cell membrane, and its stable transformation in tobacco confirmed its ability to confer enhanced resistance to heavy Ca2+ stresses, highlighting its crucial role in the high-calcium tolerance mechanisms of R. roxburghii. This research establishes a foundation for further molecular-level functional analyses of the adaptation mechanisms of R. roxburghii to high-calcium environments.